Origin and development of true karst valleys in response to late Holocene sea‐level change, the Transverse Glades of southeast Florida, USA. (2nd September 2019) - Meeder, John F.; Harlem, Peter W.
Abstract: The Miami Limestone is an oolite depositional body that is used as an analog model for geological interpretation of the rock record. Barrier‐bar complex, oolite banks, extensive bryozoan flats and tidal creeks, referred to as transverse glades, have been described. High‐resolution LiDAR data are used to produce unprecedented, detailed topographic maps of the transverse glades in the southern Atlantic Coastal Ridge. These maps were originally used to calculate historic discharge from the Everglades but revealed features inconsistent with the prevailing theory that the topography is of a depositional origin. Field observations verified an epikarst terrain truncated by collapsed subsurface conduits creating valleys, previously described as palaeotidal creeks. Observations of the 12 southern tidal creeks or transverse glades provided a sequence of six stages in the development of these karst valleys. After Late Pleistocene deposition of the Miami Limestone, sea‐level dropped producing conditions of: (a) epikarst which reduced the surface elevation preferentially, forming the southern Everglades Basin and modifying Biscayne Bay and Florida Bay precursor basins and (b) downward water movement producing vertical solution features. As Holocene sea‐level approached the South Florida carbonate platform margin a freshwater lens formed and groundwater movement became horizontal. Two sets of cavernous zones developed during the Middle and Late Holocene. Solution pipes and dolines provide a connection between the surface and groundwater along alignments which delineate subsurface conduits. Stages of valley formation are associated with the collapse of these conduits first forming a series of pocket valleys followed by narrow blind valleys and half blind or through valleys linking the Everglades to the coastal plain. Valleys then expanded in width until: (a) completion of cavernous zone collapse, (b) most boulder fields and valley margins reduced by weathering and (c) the valleys filled with wetland soils. Abstract : Karst processes associated with changing sea level and ground water table resulted in the final topography of South Florida and the origin of the transverse glades. Epikarst processes reduced the surface by 2 m. Changes in the ground water table produced two stratiform cavernous zones which collapsed forming the transverse glades which control Everglades topography.